Pathogenicity of some local entomopathogenic fungus isolates on the cotton leafworm larvae, Spodoptera littoralis (Boisd.) (Lepidoptera: Noctuidae) - Funda Şahin (SpringerOpen, 2021)
Abstract Background Pathogenicity of the entomopathogenic fungi (EPF), isolated from soil samples collected from Ordu Province, Turkey, was evaluated on the second-instar larvae of the cotton leaf worm Spodoptera littoralis (Boisd.) (Lepidoptera: Noctuidae) under laboratory conditions. Results Firstly, single-concentration response tests were conducted in order to determine the efficacy of the 64 isolates on S. littoralis larvae at the concentration of 1 × 108 conidia/ml. The five isolates displaying the highest mortality rates in single-concentration response tests, ORU-50, ORM-40, ORP-13, ORP-27 and ORM-48 (which included Beauveria bassiana, Metarhizium brunneum and Clonostachys rogersoniana), were subjected to concentration–response tests at the concentrations of 1 × 105–1 × 109 conidia/ml. The lowest LC50 and LC90 values were recorded at ORP-27 with 1.68 × 107 and 4.60 × 108 conidia/ml, respectively, followed by ORP-13 and ORM-40. Conclusions Accordingly, it was found that M. brunneum isolates were more effective than B. bassiana and C. rogersoniana against S. littoralis larvae. ORP-27, ORP-13 and ORM-40 of M. brunneum isolates can be a potential biological control agent used against S. littoralis larvae.